DEVELOPMENT OF DIGITAL SMART TOURISM AT THE MARINE MUSEUM JAKARTA - Sheva Aulia; Rizki Nurul Nugraha (Sekolah Tinggi Pariwisata Mataram, 2022)
The Jakarta Maritime Museum is one of the Dutch archeology in the VOC era, has two main buildings that have two different functions during trade in Sunda Kelapa port. Until now, the building is still very sturdy and preserved, including the collections in it, both original and replica items. In 2018 the maritime museum began to develop digital tourism by creating a museum partner website “Jakarta Maritime Museum” and developed it into digital smart tourism with programs that carry historical and cultural education. The purpose of this research is to identify the development of Digital Smart Tourism at the Jakarta Maritime Museum in this era 4.0 . In this study, the author uses a qualitative research methods by conducting observations, interviews with museum management staff and SWOT analysis technique